Is removing blood donation barriers a donation facilitator?: Australian African migrants' view. Issue 3 (13th July 2015) - Polonsky, Michael; Francis, Kate; Renzaho, Andre
Abstract : Purpose: – The aim of this study was to assess whether the removal of blood donation "barriers" facilitates blood donation intentions, using a sample of African migrants, and to identify the implications for social marketing. African migrants are currently under-represented as blood donors in Australia. Some members of the African community have unique donation needs that can only be served by this community. Design/methodology/approach: – Interviews were conducted with 425 people from the African community in Victoria and South Australia. Factor analysis was performed on the barriers and the removal of barriers. Item groupings for both constructs differed, suggesting that barriers and their removal are not necessarily opposite constructs. Findings: – The cultural society factor was negatively associated with blood donation intention (i.e. a barrier), whereas engagement and overcoming fear were positively associated with blood donation intention (i.e. facilitators). Cultural issues and lack of understanding were not seen to impede blood donation. Additionally, the removal of cultural barriers did not facilitate increases in blood donation intentions. Thus, the removal of barriers may not be sufficient on their own to encourage donation. Research limitations/implications: – This only examines the issue with regards to whether the removal of barriers is a facilitator of blood donation with one group of migrants, and relationships may vary across other migrant and non-migrant groups. Practical implications: – Policymakers often use social marketing interventions to overcome barriers as a way of facilitating blood donation. This research suggests that removing barriers is indeed important because these barriers impede people considering becoming blood donors. However, the findings also suggest that the removal of barriers is insufficient on its own to motivate blood donations (i.e. the removal of barriers is a hygiene factor). If this is the case, social marketing campaigns need to be multifaceted, removing barriers as well as leveraging facilitators, simultaneously. Social implications: – This work identified that the impact of barriers and their removal may facilitate effective social marketing campaigns in differing ways, in the context of blood donation. Originality/value: – How barriers and their removal impact social marketing activities (i.e. blood donation behaviour) has generally not been explored in research.